Estudio de las competencias digitales educativas de los estudiantes de tercer año de bachillerato general unificado de las unidades educativas de las cabeceras cantonales del distrito Guano-Penipe, de la provincia de Chimborazo - Iguasnia Gusqui, Digna Isabel (2016)
The purpose of this study was to determine the digital skills level of students the third year of Bachillerato General Unificado of Educational Units of de municipal capitals of Guano-Penipe district, of Chimborazo province. It was necessary to do a bibliographical analysis, to know digital competences proposed by the Ministry of Education. Afterwards it is carried out a field research; the information is collected through a questionnaire, which was developed based on core indicators of evaluation of the subject “Computer Applied to Education”. First level of knowledge acquired by students in each core indicator of evaluation that subject was determined, then levels of digital competences acquired by students based on six indicators was determined. According to the results, it was evidenced that 83% of students do not reach digital competences, while only 17% of students are close to achieving these competences, it is recommended to the authorities of Educational Units of Guano-Penipe district to train properly to the future graduates, so that effectively achieve these educational digital competences raised by the Ministry of Education.